VD_FINDINFO Décision / 2014 / 49 vom 17. Januar 2014 - VD Tribunal cantonal (2014)
SUSPENSION DE LA PROCÉDURE, PRINCIPE DE LA CÉLÉRITÉ | 314 al. 1 let. b CPP (CH), 393 al. 1 let. a CPP (CH), 5 CPP (CH), 80 al. 1 CPP (CH)